Thermodynamic trends for the adsorption of non polar gases on activated carbons employing a new adsorption isotherm modelling - Chakraborty, Anutosh (2017)
In this paper, the author reports a thermodynamic framework for understanding the surface – energy and the surface – structural interaction factors of activated carbons with various non polar adsorbate molecules. For better understanding, the author employs adsorption uptakes data of activated carbons and some non-polar gases such as H2, Ar, N2, CO2, O2 and CH4 to calculate the enthalpy and entropy of adsorption in pressure-temperature-uptake coordinate systems. The RMS errors are calculated with respect to the proposed model and the experimental data. The minimum RMSEs are found as the model fits well with the experimental data. From theoretical observations, the heterogeneity factors (m) are obtained 1 for microporous and 2 for mesoporous activated carbons, and the interactions of non-polar gases on activated carbons are found to be more sensitive to the adsorbent pore geometry and the adsorbate size. It is also established that the enthalpy and entropy of adsorbent – adsorbate system are closely related to the kinetic diameter of adsorbate molecules, and the pore size equivalent to adsorbate kinetic diameter is the key to store more adsorbate at low pressures. For example, the pore width of activated carbon is roughly maintained 3.8 Å for more methane storage and 3.3 Å for more CO2 captures.